MODEL PENYELESAIAN SENGKETA DAN PERKARA PIDANA IN AND OUT SIDE COURT - Reva Amalia (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2022)
This study aims to explain the dispute resolution in and out side court (Litigation and Non-Litigation Dispute Resolution) based on the existence of a dispute or criminal case between communities that fight for certain main goals from each party, and put pressure on each other. the other then failed to reach a single opinion and each side tried to consciously fight for their main goals. Which ultimately creates a conflict or dispute that must be resolved both litigation and non-litigation. So that this research can be formulated, namely, related to what is meant by litigation and non-litigation dispute resolution. What is the difference between mediation in litigation and non-litigation dispute resolution, and how to resolve criminal cases outside the court. The purpose of this study is to find out what is meant by litigation and non-litigation dispute resolution and the differences and how to resolve the case or dispute outside the court. This research method uses a normative qualitative method, the results of which conclude that: Litigation dispute resolution is a settlement process carried out in court, while non-litigation is a dispute resolution process outside the court. The process of resolving criminal cases outside the court can be carried out by way of deliberation.